An Ordered Logit Model for Predicting the Willingness of Renting Micro Mobility in Urban Shared Streets: A Case Study in Palermo, Italy - Campisi, T.; Akgün Tanbay, Nurten; Tesoriere, G. (Springer Science and Business Media Deutschland GmbH, 2020)
Sustainable transport modes, particularly micro-mobility, allows to reduce possible congestion phenomena in urban traffic. In this study, the aim is to make a contribution to increase micro-mobility use by exploring the impacts of socio-demographic, vehicle ownership (car, bicycle and micro mobility), level of infrastructure service and road users’ perception in safety, comfort and chaotic environment on renting micro-mobility in a shared urban street. The study area is a historical center called Via Maqueda in Palermo, Italy, which is rich in commercial and cultural activities. A survey with 200 individuals is carried out for the data collection regarding the aim of the study. The analysis starts with a descriptive statistics in order to illustrate the characteristics of the predictor variables. This is followed by relaxing p-value method for selecting the statistically significant predictor variables with 90% confidence level. These selected predictor variables are applied into an ordinal logit model. The results suggest that one unit increase in car ownership decrease the willingness of renting a micro mobility by log odds of ?0.74, given all the other predictors are held constant. One unit increase in age group decrease the willingness of renting micro-mobility in shared urban streets. The outcomes will guide decision makers to understand who the average road users are and what are their needs in terms of further developments of the micro-mobility system in urban shared streets. The originality of this paper consists the perceptions of road users, such as safety and comfort, on micro-mobility that can encourage to use this sustainable urban travel mode in restricted traffic areas. © 2020, Springer Nature Switzerland AG.
20th International Conference on Computational Science and Its Applications, ICCSA 2020 -- 1 July 2020 through 4 July 2020 -- -- 249529
Keywords: Micro-mobility; New mobility users; Ordered logit model; Relaxing p-value method